DOES LOVE OF MONEY INDUCE ECONOMIC CRIME? - Ishak, Nur Annizah; Abu Bakar Ah, Siti Hajar; Zakaria, Roza Hazli (The Malaysian Journal of Social Administration, 2020)
The meaning of money is subject to an individual’s valuation. Individuals’ perception of money affects their behaviour and wellbeing more than money does. Greed, lifestyle, and personal financial pressures are the leading motivations for fraud, deception, corruption and bribery cases in Malaysia. The first objective of this study is to identify the prevalence of love of money (LOM) attitude among Malaysians. Second, the study examines the relationship between the love of money and economic crime by exploring the meaning of love of money and investigating to what extent it may lead to criminal behaviour. The finding indicates that all variables of the love of money have strong coefficients with the constructs, demonstrating its prevalence in Malaysia. The result shows that all composite reliability (CR) is more than 0.8, demonstrating that each variable can explain the construct precisely, notably ‘Rich’ at 0.94 (ρ=0.003), and ‘Achievement’ at 0.929 (ρ=0.005). These findings prove that Malaysians have a high tendency for love of money. However, the study found no relationship between the love of money and economic crime, although the structural model showed an acceptable model fit and recommended the feasibility of applying these constructs in tandem with the underlying theory. In general, this study makes a significant contribution to understanding how the desire for money can lead to criminal behaviour.